Upaya Tokoh Masyarakat melalui Majelis Ta’lim dalam Meningkatkan Minat Orang Tua Menyekolahkan Anak di Kelompok Bermain Az-Zakiyah Kabupaten Bandung - Octrianty, Evi; Muttaqien, Kingking; Marwati, Lia (AHKAM, 2023)
This research is focused on the efforts that have been made by community figure through the ta'lim assembly in increasing parents interest in sending their children to the Az-Zakiyah Playgroup. The method used in this study is a qualitative descriptive method by collecting interview and observation data. The results of this study are to discuss: (1) the efforts made by community figure for parents to send their children to Az-Zakiyah Playgroup; (2) description of parents interest in Az-Zakiyah Playgroup; (3) parents perspective on Playgroups; (4) the obstacles experienced by community figure and schools in increasing parents interest in Az-Zakiyah Playgroup; and (5) how to overcome the obstacles experienced by community figure and institutions in increasing parents interest in sending them to Az-Zakiyah Playgroup.